Investigating the effect of electrospark alloying parameters on structure formation of modified nitrogen coatings - Haponova, Oksana; Tarelnyk, Viacheslav; Mościcki, Tomasz; Tarelnyk, Nataliia (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The quality parameters of surface layers synthesised using electrospark alloying (ESA) technology were analysed in this paper. The main focus was on the influence of equipment energy parameters on structure formation, specifically the effect of discharge energy and productivity. Microstructural analysis of the modified surface of C40 steel after nitriding by ESA using a paste containing nitrogen compounds injected into the interelectrode gap was conducted. The layer structure for all studied ESA parameters includes three areas: the upper “white layer”, the diffusion zone below it, and the substrate. The roughness of the surface is Ra ∼ 0.9 µm at low discharge energy Wp = 0.13 J and Ra ∼ 6 µm at Wp = 3.4 J. The microhardness, continuity, and surface roughness of the layers varied with Wp. The influence of ESA productivity on the structure was studied. The thickness of the hardened layer and the diffusion zone, as well as the microhardness and continuity, are affected by reduced productivity. For the same discharge energy, the thickness of the hardened layer increases by 10-18% with a decrease in productivity compared to the classical mode. Studies have shown that productivity loss has a positive effect on the quality characteristics of the coatings produced by the ESA process.